Nomination skills of pre-school children Part 2 - Kij, Monika (Logopedia Silesiana, 2021)
This paper is a second part of a publication devoted to the level of nomination skills of children aged four to six. Whilst the first part focused on toys: humanoid and not modelled on living beings – this paper examines the naming of animals and plush toys modeled on animals. The author analyses methods used by children to create proper names (chrematonyms) and elements of extralinguistic reality rooted in these names. The influence of socio-cultural factors (age and gender) on the development of naming skills of pre-schoolers is also examined.